Synthesis and Self-assembling Properties of 2,2':6',2aEuro3-Terpyridine-Based Carbon Nanotube Coordination Polymers - Koytepe, Suleyman; Demirel, M. Hursit; Seckin, Turgay (Springer, 2013)
A novel metallo-supramolecular polytopic ligand was synthesized from the attachment reaction involving an amino group-functionalized multi-wall carbon nanotube and 4-chloro-2,2':6',2aEuro(3)-terpyridine used for the preparation of metallo-supramolecular polymers with Co(II) or Ni(II) ions. Different colors were observed depending on either the ligands or the metal ions in this type of supramolecular assembly. The created supramolecular polymers were characterized by means of structure, morphology, and stimuli-responsive performance employing scanning electron microscopy, amperometric techniques, UV-Vis and Fourier transform infrared spectroscopy. UV-Vis spectroscopy and cyclic voltammetry studies confirmed that both the optical and electrochemical properties of metallo-supramolecular materials are affected by the substituent at the pyridine periphery.
Keywords: Supramolecular polymers; MWCNT; Coordination chemistry; Terpyridine ligands